1989
DOI: 10.1111/j.1813-6982.1989.tb00174.x
|View full text |Cite
|
Sign up to set email alerts
|

On Income Distribution and Economic Sanctions

Abstract: 1) ALTHOUGH numerous individuals and organisations have voiced opinions about the impact of economic sanctions on the distribution of in-come in South Africa, there has to date been no attempt to frame the arguments in a theoretical model of any rigour. The purpose of this paper is to present the outline of one possible means of analysis that can be fruit-fully employed to investigate this aspect of the sanctions problem. The approach employed is based on the orthodox neoclassical trade theorem developed by St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…The key variables are the distinctions between producers and consumers and between importers and exporters. In addition, if domestic exporters use more labour relative to capital than the producers of importables, labour can expect to suffer a greater loss from sanctions than the owners of capital (Cooper, 1989). Consequently, the political economy effect will depend on the relative importance of capital and labour in the production functions of export and import-substituting industries and ultimately also on the political power of labour relative to capital owners.…”
Section: Saje V57(2) P190mentioning
confidence: 99%
“…The key variables are the distinctions between producers and consumers and between importers and exporters. In addition, if domestic exporters use more labour relative to capital than the producers of importables, labour can expect to suffer a greater loss from sanctions than the owners of capital (Cooper, 1989). Consequently, the political economy effect will depend on the relative importance of capital and labour in the production functions of export and import-substituting industries and ultimately also on the political power of labour relative to capital owners.…”
Section: Saje V57(2) P190mentioning
confidence: 99%
“…
1) RECENTLY, Black and Cooper (1987), Cooper (1989), Dollery (1989a) and Holden (1989) have applied the two-sector general equilibrium trade framework to provide a formal analysis of the economic effects of sanctions. Holden (1989) argues that unemployment can be generated within a two-sector, two-factor model with capital specificity and downward rigidity of real wages.
…”
mentioning
confidence: 99%
“…The long run assumption of perfect capital mobility is justified as a result of physical capital assets transferring themselves into financial capital over time. 9 Cooper (1989), however, assumes that the impact of sanctions imposed is analogous to an internally imposed trade-eliminating tariff.…”
mentioning
confidence: 99%
“…While financial sanctions and an embargo on intermediate and capital goods may well have a direct impact on white capital and skilled workers, they are bound to have an indirect though not necessarily less significant effect on "black workers". Moreover, Cooper (1989) has shown that a shortage of capital will increase the functional income share of capital at the expense of labour, implying that such sanctions will "harm" labour and "benefit" capital. Since not all whites (alas) are capitalists, nor all black workers; and since not all whites are pro-apartheid, nor all blacks anti-apartheid; and since not all capitalists are pro-apartheid, nor all workers anti-apartheid, the definition of interest groups is problematic, to say the least.…”
mentioning
confidence: 99%